Filtration of Protein in Tempe Wastewater Using Cellulose Acetate Membrane - Dwi Indarti; Badrut Tamam Ibnu Ali; Tri Mulyono (UNEJ e-Proceeding, 2016)
The protein content in the wastewater tempe high enough. Filtration of tempe wastewater  can use cellulose acetate membranes. Type cellulose acetate membranes used is ultrafiltration membranes. Pressure and protein concentration influenced on the flux, rejection, and fouling resistance. Membrane characteristics included flux, pore asymmetries, time compaction and permeability coefficient. The results showed that fouling resistance is influenced by the pressure and concentration of the feed solution. The higher the pressure will cause increased fouling resistance, while higher concentrations will cause fouling resistance decreases. The pressure and the higher the concentration of protein causes rejection decreasedFiltration of Protein in Tempe Wastewater Using Cellulose Acetate Membrane